The Effect of Affective Commitment and Work Motivation on Employee Performance at PT. Asrindo Citraseni Satria Minas - Hafizah, Yolanda; Fitri, Kurniawaty; Siregar, Prima Andreas (Westscience Press, 2026)
This study aims to analyze the influence of affective commitment and work motivation on employee performance at PT. Asrindo Citraseni Satria Minas. This study uses a quantitative approach with a questionnaire distribution method. The population in this study were office employees at PT. Asrindo Citraseni Satria Minas, with a sampling technique using saturated samples. Data were analyzed using multiple linear regression tests with the help of SPSS 25. The results showed that commitment has a negative and insignificant effect on employee performance. In addition, work motivation has a positive and significant effect on employee performance. Simultaneously, affective commitment and work motivation together have a significant effect on employee performance.